Somatosensory cortical remodelling after rehabilitation and clinical benefit of in writer's cramp. Issue 5 (18th June 2010) - Bleton, Jean Pierre; Vidailhet, Marie; Bourdain, Frédéric; Ducorps, Antoine; Schwartz, Denis; Delmaire, Christine; Lehéricy, Stéphane; Renault, Bernard; Garnero, Line; Meunier, Sabine
Abstract : In order to explore the pathophysiological basis of a new rehabilitation therapy in writer's cramp (WC), healthy controls, untreated WC patients and WC patients who recovered a legible handwriting after rehabilitation were explored using magnetoencephalography, and the somatosensory evoked fields of fingers I, II, III and V in the sensory cortex were studied. In the cortex controlling the dystonic limb, the size of the hand representation in the trained patients was similar to that of healthy controls, and significantly different from that of untrained patients. Trained patients exhibited 'super-normal' reorganisation of the finger maps. In the cortex controlling the non-dystonic limb, there was little difference between trained and untrained patients, and the hand representation was enlarged and disorganised. The authors hypothesise that prolonged tailored rehabilitation in WC may induce long-term plasticity phenomena, lateralised to the cortex controlling the dystonic hand.